Evaluación de tres técnicas para extracción de ovocitos (aspiración folicular, slicing, exposición folicular) con dos crioprotectores (etilenglicol y polietilenglicol) en ovejas (ovis aries) de matadero en el CEASA - Romero Proaño, Edgar Miguel (2015)
This research was carried out at the Technical University of Cotopaxi developed at the Career of Veterinary Medicine at the Laboratory of Reproductive Biotechnology. The main goal of this study was to evaluate which of the techniques: slicing, absorb and follicular exhibition is the most appropriate in categorizing, oocytes quality and performance by using both ethylene glycol and polyethylene glycol cryo-protectants. For the investigation study I got 36 ovaries of 18 females samples I have gotten post-mortem, which were placed in a thermos with a suitable means of transport to the laboratory and then they were extracted the oocytes. To get the oocytes, it was performed using three basic steps: Extraction, Conservation and Freezing….